Educational Democracy in the Digital Era: Constitutional Challenges in Ensuring Equitable Access to Education in Indonesia - Sri Ayu Irawati; Martin Uribe (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study examines the constitutional challenges of ensuring equitable access to education within the framework of educational democracy in Indonesia’s digital era. Despite constitutional guarantees under Article 31 of the 1945 Constitution, significant disparities persist in access to digital education, particularly between urban and rural areas. This raises critical questions: (1) to what extent does the digital transformation of education align with the principles of educational democracy; and (2) how effectively does the state fulfill its constitutional obligation to ensure equitable access to education in the digital context? This research employs a normative juridical method with a socio-constitutional approach, analyzing legal frameworks, policy developments, and relevant scholarly literature. The findings reveal that while digitalization has expanded educational opportunities, it has also reproduced structural inequalities due to unequal infrastructure, digital literacy gaps, and socio-economic disparities. The state’s role remains pivotal but insufficiently optimized, as existing policies tend to emphasize technological expansion rather than substantive equality. Consequently, educational democracy in Indonesia faces a paradox between formal constitutional guarantees and unequal practical outcomes. This study contributes to the academic discourse by offering a critical constitutional perspective on digital education, emphasizing the need to shift from formal equality to substantive justice. It proposes a reconceptualization of educational democracy that integrates digital inclusion as a constitutional mandate, thereby providing a framework for more equitable and responsive education policies in Indonesia’s evolving digital landscape.